Pengaruh Kualitas Layanan, Bagi Hasil, Dan Kepercayaan Terhadap Kepuasan Nasabah Bank Syariah Di Masa Pandemi Covid-19 - Novita Sari; Kusumaningtias, Rohmawati (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
The purpose of this research is to determine the effect of servive quality, profit sharing, and customer trust in Islamic Bank customer during the Covid-19 pandemic. This research uses a population of Islamic Bank customers in the Surabaya City and the number of samples of the research is 100 respondents with the Non Probability Sampling methode and the technique used is Accidental Sampling. Data collection was carried out by distributing quetionnaires online. The data analysis technique used is multiple regression analysis and based on the result of the analysis it was found that service quality, proft sharing, and trust is a positive and significant impact on customer satisfaction in Islamic Banks customer during the Covid-19 pandemic